2009
DOI: 10.1002/lt.21676
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal drains in liver transplantation: Useful tool or useless dogma? A matched case-control study

Abstract: On the basis of the growing evidence from randomized trials that routine prophylactic drainage is unnecessary in liver surgery or even harmful in chronic liver disease, we challenged the concept of prophylactic drainage in orthotopic liver transplantation (OLT). Since September 2006, we omitted drains in every patient who underwent OLT, regardless of the procedure. Thirty-five cadaveric OLTs were performed during a 12-month period. These patients were matched 1:2 with 70 patients who had prophylactic drainage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
0
26
2
Order By: Relevance
“…In an analysis by De Rougemont et al, the median in-dwelling time of abdominal drains was short (3 days), and most interventions for complications were performed after removal of the drain (median, 5 days) [9]. Bile leaks due to ischemic necrosis of the common bile duct usually occur between POD 5 and 10, which corresponds to the period after removal of the drain in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In an analysis by De Rougemont et al, the median in-dwelling time of abdominal drains was short (3 days), and most interventions for complications were performed after removal of the drain (median, 5 days) [9]. Bile leaks due to ischemic necrosis of the common bile duct usually occur between POD 5 and 10, which corresponds to the period after removal of the drain in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Data on this subject are limited. A systematic review of the Cochrane database in 2011 [10] showed that no prospective randomized controlled trial has been performed yet to evaluate the suitability of abdominal drains in LT. One pair-matched analysis [9] and three retrospective studies have been published [1,9,11,12]. None of these was focused on the risk of infection and bile duct complications associated with the placement of a drain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review and meta-analysis found no evidence to support abdominal drain use after hepato-pancreato-biliary resections [15]. Even in liver transplantation, where use of abdominal drains is widely practiced, a recent study failed to demonstrate any benefits in patients treated with intraoperative drains [16]. Presence of a drain did not expedite re-interventions for hemorrhage or bile leak in patients receiving a liver transplant.…”
Section: Discussionmentioning
confidence: 97%
“…In some cases, the use of drains may even be related to longer hospital stay and higher postoperative morbidity (47).…”
Section: Prophylatic Drainagementioning
confidence: 99%